Banking on the go: factors affecting the behavioral intention towards m-banking - Cheng, Chee Wei; Lee, Yi Yun; Lim, Wee Jun; Tan, Yie Ling; Teh, Sin Hui (2019)
The research is aimed to investigate the factors that affect the behavioral intention towards M-Banking among UTAR undergraduates in Kampar campus, which represent the 90s generation. The study examines the behavioral intention towards M-Banking by including independent variables of perceived usefulness, perceived ease of use, perceived risk, relative advantage and trust with the aid of TPB theory. Target respondents that included in the research are students from Faculty of Business and Finance (FBF) and students from Non FBF in UTAR Kampar equally by collecting data with a total of 400 sets of survey questionnaires. SmartPLS 3 is used to assist in our data analysis along the research. Reliability test, discriminant validity, significance of variables, bootstrapping is applied in the data analysis. The results concluded that the independent variables of perceived ease of use and relative advantage have significance relationship with the behavioral intention towards M-Banking among undergraduates’ students. Conversely, perceived usefulness, perceived risk and trust have no significant effect on the behavioral intention towards M-Banking among undergraduates’ students. Some limitations and suggestions are included in the study to provide a better idea for future researchers and M-Banking service providers to enhance the behavioral intention towards M-Banking in Malaysia.